Reproductive research in dairy cattle at KSU - Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station, 2012)
Research in reproductive physiology and breeding management of dairy cattle at Kansas State University has the following objectives: 1) to better understand those factors that influence the reestablishment of ovarian function, estrous cycles, and fertility after calving and 2) to apply that knowledge to areas of management in which pregnancy rates and calving intervals can be improved in dairy herds. Our past efforts have included 1) pioneering research into the applications of gonadotropin-releasing hormone (GnRH) at the time of insemination and early postpartum as a prophylactic treatment for inducing estrous cyclicity; 2) application of treatments utilizing prostaglandin F2α (PGF2α ) for breeding management of open cows, estrous induction for first services, and postpartum therapy for cows with periparturient problems; 3) utilization of progesterone-releasing intravaginal devices (PRIDs) to induce estrus and enhance fertility; 4) studies aimed at understanding estrous behavior, including the influence of the thyroid gland; 5) efforts to understand the influence of progestogens on the function of the corpus luteum; and 6) estrous synchronization of heifers and cows utilizing PGF2α.
The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy; Reproduction; Milk production; Estrous; Fertility